Ionic liquid polymer catalyst as well as preparation method and application thereof

By encapsulating the metal active component in an ionic liquid polymer catalyst inside the polymer backbone of a triphenylphosphine ionic liquid based on vinyl functionalization, the problems of high recycling cost of phosphine ligands and difficulty in recycling metal active components in the prior art are solved, and efficient and stable catalytic effect of cycloaddition reaction and good reusing performance are achieved.

CN119912652AActive Publication Date: 2025-05-02LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510092164.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

In the prior art, the catalyst used for the cycloaddition reaction of CO2 and epoxy compounds has the problem of high cost of recycling phosphine ligands, and it is difficult to effectively recover and reuse the metal active components.

Method used

An ionic liquid polymer catalyst is designed to form a coordination configuration by encapsulating the metal active component into the polymer framework of a vinyl functionalized triphenylphosphine ionic liquid, thereby achieving efficient use of the catalyst and effective recovery of the metal active component.

Benefits of technology

This catalyst exhibits excellent catalytic performance and stability in the cycloaddition reaction using flue gas as the CO2 source, which can effectively improve the reaction activity, avoid metal loss, and have good reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912652A_ABST
    Figure CN119912652A_ABST
Patent Text Reader

Abstract

The invention discloses an ionic liquid polymer catalyst as well as a preparation method and application thereof. The catalyst is obtained by carrying out polymerization reaction on vinyl functionalized triphenylphosphine ligand, vinyl functionalized triphenylphosphine ionic liquid and a metal source, wherein the triphenylphosphine ionic liquid based on vinyl functionalization is obtained from the triphenylphosphine ligand based on vinyl functionalization. The ionic liquid polymer catalyst has more excellent catalytic performance and better substrate universality, the preparation method is simple and convenient, flue gas can be directly used as a CO2 source, CO2 does not need to be purified, energy is effectively saved, and meanwhile the environment is protected; meanwhile, cycloaddition reaction conditions are mild, green and pollution-free; the yield of the product cyclic carbonate is as high as 99%, and the method shows a good prospect for solving the problems of good reactivity and universality, difficult catalyst recycling, serious loss of active metals and ligands and the like in the heterogeneous cycloaddition reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cycloaddition reaction catalytic materials, and specifically relates to an ionic liquid polymer catalyst and a preparation method and application thereof. Background Art

[0002] Cyclic carbonate is an important chemical raw material with the advantages of high polarity, high boiling point, high dipole moment, low volatility, low toxicity, good solubility and biodegradability. It can be widely used in the preparation of cosmetics, lubricants, lithium battery electrolytes and the synthesis of fine organic intermediates.

[0003] In industrial manufacturing, CO2 is considered to be a substitute for toxic carbonylation raw materials (such as CO and phosgene) with the characteristics of large reserves, low cost, easy availability and renewability. How to use it as a reaction raw material to synthesize high-value-added cyclic carbonates has attracted widespread attention from scholars. However, the CO2 currently used in this reaction is still high-purity CO2 obtained by removing high-concentration and low-concentration (flue gas) waste gas through a series of steps such as desulfurization, deoxygenation and dehydration. The process of preparing CO2 through distillation consumes a lot of manpower, material resources and financial resources. Therefore, it is of great industrial application value to directly use low-concentration waste gas (flue gas) as CO2 source and prepare cyclic carbonates through cycloaddition of epoxide compounds.

[0004] Currently, the catalysts used for the cycloaddition reaction of CO2 and epoxides mainly include alkali metal salts, metal complexes, molecular sieves, ionic liquids and homogeneous zinc / phosphine complexes. Among them, zinc / phosphine complexes stand out among many catalysts due to their unique functional designability and excellent CO2 adsorption capacity and other physical properties. However, the recycling of expensive phosphine ligands is a huge and non-negligible problem. Therefore, it is urgent to design and develop a new type of efficient multiphase catalytic system that can effectively recycle and reuse metal and phosphine ligands while improving the activity of cycloaddition reactions.

[0005] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0006] The purpose of the present invention is to provide an ionic liquid polymer catalyst and a preparation method and application thereof. The ionic liquid polymer catalyst has more excellent catalytic performance and better substrate universality, the preparation method is simple, and flue gas can be directly used as a CO2 source without the need to purify CO2, thereby effectively saving energy and protecting the environment.

[0007] In order to achieve the above object, the present invention provides an ionic liquid polymer catalyst, which is obtained by polymerization reaction of a triphenylphosphine ligand with a vinyl functional group as shown in Formula I or II, a triphenylphosphine ionic liquid based on vinyl functional group and a metal source; wherein the triphenylphosphine ionic liquid based on vinyl functional group is obtained from a triphenylphosphine ligand with a vinyl functional group as shown in Formula I or II;

[0008] Formula I

[0009] Formula II In formula I or II, R1 to R3 are selected from vinyl groups.

[0010] The invention encapsulates metal active components inside a polymer skeleton based on vinyl functionalized triphenylphosphine ionic liquid, and the metal active components form a coordination configuration with the phosphine ligand. The catalyst can be used in an epoxide ring addition reaction using flue gas as a carbonyl source.

[0011] Preferably, the chemical structural formula of the vinyl-functionalized triphenylphosphine ionic liquid is as shown in Formula III or IV:

[0012] Formula III

[0013] Formula IV; Or / and, the substitution positions of R1 to R3 are each independently ortho or para.

[0014] Preferably, the structural formula of the vinyl functionalized triphenylphosphine ligand is selected from any one of the following: , or ; Or / and, the structural formula of the vinyl-functionalized triphenylphosphine ionic liquid is selected from any one of the following: ,

[0015] or ; Or / and, the metal source is selected from any one or more of a zinc source, a magnesium source, a copper source, a manganese source, a nickel source, an iron source and a cobalt source.

[0016] Preferably, the zinc source is selected from any one or more of zinc chloride, zinc iodide, zinc bromide, zinc hydroxide, zinc acetate, basic zinc carbonate, zinc powder, zinc nitrate hexahydrate and zinc nitride; the magnesium source is selected from any one or more of magnesium nitrate hexahydrate, magnesium carbonate, magnesium silicate, magnesium chloride hexahydrate and magnesium stearate; the copper source is selected from any one or more of copper nitrate trihydrate, cuprous chloride, cupric bromide, copper acetate, copper powder and copper glycinate; the manganese source is selected from any one or more of manganese chloride tetrahydrate, manganese powder , manganese nitrate solution, tetrahydrated manganese acetate and manganese powder; the nickel source is selected from nickel chloride hexahydrate, nickel acetylacetonate, nickel acetate, nickel triphenylphosphine and nickel powder; the iron source is selected from ferric chloride hexahydrate, ferrous bromide, ferrous chloride tetrahydrate, ferric acetate, ferric nitrate nonahydrate and iron powder; the cobalt source is selected from cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt acetate, dicobalt octacarbonyl and cobalt chloride. All of the above metal sources can provide active metals for preparing ionic liquid polymer catalysts.

[0017] The second object of the present invention is to provide a method for preparing the ionic liquid polymer catalyst, which comprises: in an inert gas atmosphere, placing a vinyl-functionalized triphenylphosphine ligand having a chemical structure as shown in formula I or II, a vinyl-functionalized triphenylphosphine ionic liquid and a metal source in an organic solvent, and causing a polymerization reaction at 60-100° C. under the action of a free radical initiator.

[0018] Preferably, the organic solvent is selected from any one or more of 1,4-dioxane, tetrahydrofuran, ethylene glycol dimethyl ether, ethyl acetate, N,N-dimethylformamide, dimethyl sulfoxide, n-hexane, toluene, anisole, dichloromethane and chloroform, and these organic solvents can be used in the preparation method of the ionic liquid polymer catalyst; or / and, the free radical initiator is selected from any one or more of azobisisobutyronitrile, ammonium persulfate, potassium persulfate, benzoyl peroxide and methyl ethyl ketone peroxide, and these free radical initiators can be used in the preparation method of the ionic liquid polymer catalyst; or / and, the polymerization reaction time is 1 to 72 hours; or / and, the molar ratio of the vinyl-functionalized triphenylphosphine ligand, the vinyl-functionalized triphenylphosphine ionic liquid and the metal source is 2: 0.72:1.

[0019] Preferably, the preparation method of the vinyl-functionalized triphenylphosphine ionic liquid comprises: dissolving a vinyl-functionalized triphenylphosphine ligand, p-dihalobenzyl and p-tert-butylcatechol in an anhydrous dichloromethane solution under an inert gas atmosphere, and stirring the solution at 40° C. for reaction; after the reaction is completed, washing with methyl tert-butyl ether and drying to obtain a vinyl-functionalized triphenylphosphine ionic liquid.

[0020] The third object of the present invention is to provide the use of the ionic liquid polymer catalyst in catalyzing the preparation of cyclic carbonates by cycloaddition reaction of flue gas rings and epoxy compounds.

[0021] Preferably, the cycloaddition reaction has a reaction pressure of 0.5-4.0 MPa, a temperature of 40-150° C., a reaction solvent selected from any one or more of n-hexane, dioxane, acetonitrile, tetrahydrofuran, cyclohexane and dichloromethane, and a reaction time of 4-20 h; or / and, the CO2 content in the flue gas is 15%-25%.

[0022] More preferably, the cycloaddition reaction has a reaction pressure of 3-4.0 MPa, a temperature of 110-150° C., a reaction solvent selected from any one or more of n-hexane and acetonitrile, and a reaction time of 4-20 h.

[0023] Preferably, the structural formula of the epoxy compound is as follows:

[0024] In the formula, R4~R5 are each independently selected from H, halogenated or unsubstituted alkanes or alkenes with a carbon chain length of C1~C6, -(CH2)OR6, substituted or unsubstituted phenyl or benzyl or phenoxy or benzyloxy; wherein R6 is selected from alkanes or alkenes with a carbon number of 1 to 8, or alkanes with a carbon chain length of 1 to 3 substituted with alkoxy silicon at the end.

[0025] Preferably, the structural formula of the epoxy compound is as follows: , , , , , , , , , , , , , , , , , , , , , .

[0026] The ionic liquid polymer catalyst of the present invention and its preparation method and application have the following advantages: The ionic liquid polymer catalyst of the present invention uses a vinyl functionalized triphenylphosphine ligand as a monomer, performs free radical polymerization on the phosphine ligand, an active metal and a vinyl functionalized triphenylphosphine ionic liquid, and embeds the metal in the ionic liquid polymer in one step. The prepared ionic liquid catalyst belongs to a polymer heterogeneous catalyst, wherein the coordination of the abundant but dispersed phosphine ligands in the catalyst mesopores in the copolymer catalyst improves the reaction activity of the catalytic material, avoids the loss of active metals, greatly improves the stability of the catalyst, and has excellent reusability.

[0027] The ionic liquid catalyst prepared by the present invention has excellent reaction performance (activity, chemical selectivity, substrate universality and catalyst reusability), and can effectively convert aromatic and aliphatic epoxides with different functional groups into cyclic carbonates through a cycloaddition reaction with flue gas, with a yield of up to 99%.

[0028] In addition, compared with the existing catalytic system, the ionic liquid polymer catalyst prepared by the present invention has more excellent catalytic performance and better substrate universality, and the preparation method is simple. Moreover, flue gas can be directly used as a CO2 source, without the need to purify CO2, effectively saving energy while protecting the environment; at the same time, the cycloaddition reaction conditions are mild, green and pollution-free; the yield of the product cyclocarbonate is as high as 99%, showing good prospects for solving the problems of reactivity, good universality, difficulty in recycling catalysts, and serious loss of active metals and ligands in multiphase cycloaddition reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 These are the XRD (A) and XPS (B-D) characterization diagrams of catalyst A prepared in Example 1 of the present invention.

[0030] Figure 2 BET characterization diagram of catalyst A prepared in Example 1 of the present invention; A: Type IV adsorption isotherm; B: pore structure characterization.

[0031] Figure 3 These are SEM (A) and TEM (B) characterization images of catalyst A prepared in Example 1 of the present invention.

[0032] Figure 4 HR-TEM characterization image (A) and EDX maps characterization images (B~F) of catalyst A prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0035] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0036] The features mentioned in the present invention can be combined arbitrarily, as long as there is no contradiction in the combination of these features, all possible combinations should be considered as the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.

[0037] Example 1 An ionic liquid polymer catalyst, the preparation method and application thereof include:

[0038]

[0039] Under argon protection, trivinylphenylphosphine (2.1 mmol), p-dibromobenzyl (1 mmol) and 4-5 mg p-tert-butylcatechol were first dissolved in anhydrous dichloromethane (20 mL). The mixture was stirred at 40 °C for 4 hours, then washed with methyl tert-butyl ether and dried to obtain a white solid A quantitatively.

[0040] Under argon protection, the above white solid A (0.36 mmol), trivinylphenylphosphine (1 mmol), zinc bromide (0.5 mmol) and 18 mg of free radical initiator azobisisobutyronitrile were weighed and dissolved in anhydrous N, N-dimethylformamide (8 mL) solution. After stirring at 100 °C for 24 hours, the solution was washed with methyl tert-butyl ether and drained at room temperature to obtain catalyst Zn@PIP-1, which was recorded as catalyst A.

[0041] The application of catalyst A is as follows: In a 100 mL reactor, 40 mg of the catalyst prepared in the above examples, propylene oxide (2.5 mmol) and 4 mL of n-hexane were added. After sealing, the air in the system was replaced with flue gas three times until the pressure reached 3 MPa. The temperature was then raised to 110 °C and the reaction was carried out for 12 h.

[0042] Example 2 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: Magnesium nitrate (0.5 mmol) was used to replace zinc bromide (0.5 mmol), and the rest was the same as in Example 1. The obtained ionic liquid polymer catalyst material was recorded as catalyst B.

[0043] Example 3 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: Copper nitrate (0.5 mmol) was used instead of zinc bromide (0.5 mmol), and the rest was the same as in Example 1. The obtained ionic liquid polymer catalyst material was recorded as catalyst C.

[0044] Example 4 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: Manganese nitrate (0.5 mmol) was used instead of zinc bromide (0.5 mmol). The rest was the same as in Example 1. The obtained ionic liquid polymer catalyst material was recorded as catalyst D.

[0045] Example 5 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: Nickel nitrate (0.5 mmol) was used instead of zinc bromide (0.5 mmol). The rest was the same as in Example 1. The obtained ionic liquid polymer catalyst material was recorded as Catalyst E.

[0046] Example 6 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: Iron nitrate (0.5 mmol) was used instead of zinc bromide (0.5 mmol), and the rest was the same as in Example 1. The obtained ionic liquid polymer catalyst material was recorded as catalyst F.

[0047] Example 7 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: Cobalt nitrate (0.5 mmol) was used instead of zinc bromide (0.5 mmol). The rest was the same as in Example 1. The obtained ionic liquid polymer catalyst material was recorded as Catalyst G.

[0048] Example 8 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: Formula II is used instead of Formula I, and the rest is the same as Example 1. The obtained ionic liquid polymer catalyst material is recorded as catalyst H.

[0049]

[0050] Formula II Example 9 The application of the ionic liquid polymer catalyst of Example 1 is different in that: The pressure was 0.5 MPa instead of 3 MPa, and the rest was the same as in Example 1.

[0051] Example 10 The application of the ionic liquid polymer catalyst of Example 1 is different in that: The pressure was 4 MPa instead of 3 MPa, and the rest was the same as in Example 1.

[0052] Embodiment 11 The application of the ionic liquid polymer catalyst of Example 1 is different in that: The reaction solvent was acetonitrile instead of n-hexane, and the rest was the same as in Example 1.

[0053] Example 12 The application of the ionic liquid polymer catalyst of Example 1 is different in that: The reaction time was 4 h instead of 12 h, and the rest was the same as in Example 1.

[0054] Comparative Example 1 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: The polymerization reaction temperature was 10° C., and the rest was the same as in Example 1. The obtained ionic liquid polymer catalytic material was recorded as Catalyst I.

[0055] Comparative Example 2 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: The polymerization reaction temperature was 200° C., and the rest was the same as in Example 1. The obtained ionic liquid polymer catalytic material was recorded as Catalyst J.

[0056] Comparative Example 3 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: Ethanol was used as the polymerization reaction solvent instead of N,N-dimethylformamide. The rest was the same as in Example 1. The obtained ionic liquid polymer catalyst material was recorded as catalyst K.

[0057] Comparative Example 4 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: Hydrogen peroxide was used as the free radical initiator instead of azobisisobutyronitrile. The rest was the same as in Example 1. The obtained ionic liquid polymer catalytic material was recorded as catalyst L.

[0058] Comparative Example 5 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: The molar ratio of the vinyl-functionalized triphenylphosphine ligand, the vinyl-functionalized triphenylphosphine ionic liquid and the metal source is 1:0:1, and the rest is the same as in Example 1. The obtained ionic liquid polymer catalytic material is recorded as catalyst M.

[0059] Comparative Example 6 An ionic liquid polymer catalyst, the preparation method and application of which are substantially the same as those of Example 1, except that: The molar ratio of the vinyl-functionalized triphenylphosphine ligand, the vinyl-functionalized triphenylphosphine ionic liquid and the metal source is 100: 100: 1, and the rest is the same as in Example 1. The obtained ionic liquid polymer catalytic material is recorded as Catalyst N.

[0060] Experimental Example 1 Structural Characterization 1. XRD and XPS characterization See also Figure 1 The XRD spectrum of catalyst A in Example 1 shows that the catalyst A in Example 1 has a ◦ ~23 ◦ Similarly, PIP-1 prepared by the same method without adding metal salt also shows a broad diffraction peak at 2θ = 15 ◦ ~23 ◦ A broad diffraction peak is shown at , indicating the presence of disordered connections and amorphous structures between aromatic benzene rings in this organic framework material.

[0061] See also Figure 1 B~D, XPS spectra show that P and Zn elements exist on catalyst A in Example 1.

[0062] 2. BET Characterization The structural characteristics of catalyst A of Example 1 were evaluated by nitrogen adsorption isotherms at 77 K. The results are shown in Figure 2 .

[0063] The results showed a reversible type IV adsorption isotherm, which indicated the existence of a hierarchical pore structure. According to the quenched solid density functional theory (QSDFT), the pore size was mainly distributed in the range of 0.5 to 2.272 nm, which was beneficial for the encapsulation of Zn species and the diffusion of substances during the reaction.

[0064] 3. SEM and TEM characterization See also Figure 3 A, SEM images show that the catalyst A sample in Example 1 mainly presents an amorphous stacking structure. Figure 3 B, TEM image shows that there are a large number of irregularly distributed pores on the surface of catalyst A in Example 1. These rough surfaces and well-defined pores are not only beneficial for increasing the contact area between reactants and catalytic active sites, but also for the diffusion of reactants and products.

[0065] 3. HR-TEM and EDX maps characterization See also Figure 4 A, HR-TEM shows that Zn in catalyst A in Example 1 exists in the form of single atoms and is highly dispersed in the polymer.

[0066] See also Figure 4 B~F, EDX spectrum images show the uniform distribution of C, P, Br and Zn elements on catalyst A in Example 1.

[0067] Experimental Example 2 Performance Evaluation 1. Catalytic performance The catalysts prepared in Examples 1 to 8 and Comparative Examples 1 to 6 were used for the cycloaddition reaction of flue gas and propylene oxide to illustrate the catalytic performance of different catalysts in the cycloaddition reaction of propylene oxide with flue gas as a carbonyl source, as follows: In a 100 mL reactor, 40 mg of the catalyst prepared in the above examples, propylene oxide (2.5 mmol) and 4 mL of n-hexane were added. After sealing, the air in the system was replaced with flue gas three times until the pressure reached 3 MPa. The temperature was then raised to 110 °C and the reaction was carried out for 12 h.

[0068] After the reaction was completed, the reactor was cooled to room temperature, biphenyl was added as an internal standard, and the reaction solution was analyzed by HP-7890N gas chromatography equipped with an HP-5 capillary column and a FID detector. The catalytic performance data of different catalysts are shown in Table 1.

[0069] Table 1 Catalytic performance of different catalysts in Examples 1 to 8 and Comparative Examples 1 to 6

[0070] As can be seen from Table 1, the catalyst of the present invention has good catalytic performance for the epoxide cycloaddition reaction with flue gas as the carbonyl source.

[0071] 2. Cycle stability Taking the catalyst A prepared in Example 1 as an example, the reusability of the ionic liquid polymer catalyst in catalyzing the cycloaddition reaction of propylene oxide is described as follows: In a 100 mL reactor, 40 mg of the above-prepared catalyst, propylene oxide (2.5 mmol) and 4 mL of n-hexane were added. After sealing, the air in the system was replaced with flue gas three times until the pressure reached 3 MPa. The temperature was then raised to 110 °C and the reaction was continued for 12 h.

[0072] After the reaction, the reactor was cooled to room temperature, the solid catalyst was separated by centrifugation and washed three times with methyl tert-butyl ether, and dried in a vacuum drying oven at 60° C. for 12 h. The dried catalyst was recycled.

[0073] Biphenyl was added to the reaction solution as an internal standard and analyzed by HP-7890N gas chromatography equipped with an HP-5 capillary column and a FID detector. The reaction data of the catalyst reuse are shown in Table 2.

[0074] Table 2 Reusability of Catalyst A of Example 1

[0075] It can be seen from Table 2 that the catalyst prepared by the present invention can be reused at least five times, and the catalytic activity can still be maintained at a high level.

[0076] 3. Substrate adaptability Taking the catalyst A prepared in Example 1 as an example, the catalytic performance of the ionic liquid polymer catalyst in catalyzing different epoxide reactions is illustrated. In the reaction process, except that 2.5 mmol of different epoxide substrates are used instead of 2.5 mmol of propylene oxide, the rest is the same as the propylene oxide reaction in the catalytic performance experiment. The structure is shown in Table 3 below.

[0077] Table 3 Catalytic performance of catalyst A of Example 1 in different olefin hydroformylation reactions

[0078] As can be seen from Table 3, the catalytic materials prepared by the present invention are applied to different epoxide cycloaddition reactions using flue gas as a carbonyl source, and all exhibit excellent catalytic activity and good applicability.

[0079] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. An ionic liquid polymer catalyst, characterized in that The catalyst is obtained by polymerization reaction of a vinyl functionalized triphenylphosphine ligand with a chemical structure as shown in formula I or II, a vinyl functionalized triphenylphosphine ionic liquid and a metal source; Wherein, the vinyl-functionalized triphenylphosphine ionic liquid is obtained from a vinyl-functionalized triphenylphosphine ligand having a chemical structure as shown in Formula I or II; Formula I Formula II In formula I or II, R1 to R3 are selected from vinyl groups.

2. The ionic liquid polymer catalyst according to claim 1, characterized in that The chemical structural formula of the vinyl-functionalized triphenylphosphine ionic liquid is shown in Formula III or IV: Formula III Formula IV; Or / and, the substitution positions of R1 to R3 are each independently ortho or para.

3. The ionic liquid polymer catalyst according to claim 1, characterized in that The structural formula of the vinyl functionalized triphenylphosphine ligand is selected from any one of the following: , or ; Or / and, the structural formula of the vinyl-functionalized triphenylphosphine ionic liquid is selected from any one of the following: 、 or ; Or / and, the metal source is selected from any one or more of a zinc source, a magnesium source, a copper source, a manganese source, a nickel source, an iron source and a cobalt source.

4. The ionic liquid polymer catalyst according to claim 3, characterized in that The zinc source is selected from any one or more of zinc chloride, zinc iodide, zinc bromide, zinc hydroxide, zinc acetate, basic zinc carbonate, zinc powder, zinc nitrate hexahydrate and zinc nitride; The magnesium source is selected from any one or more of magnesium nitrate hexahydrate, magnesium carbonate, magnesium silicate, magnesium chloride hexahydrate and magnesium stearate; The copper source is selected from any one or more of copper nitrate trihydrate, cuprous chloride, cupric bromide, copper acetate, copper powder and copper glycinate; The manganese source is selected from any one or more of manganese chloride tetrahydrate, manganese powder, manganese nitrate solution, manganese acetate tetrahydrate and manganese powder; The nickel source is selected from any one or more of nickel chloride hexahydrate, nickel acetylacetonate, nickel acetate, nickel triphenylphosphine, and nickel powder; The iron source is selected from any one or more of ferric chloride hexahydrate, ferrous bromide, ferrous chloride tetrahydrate, ferric acetate, ferric nitrate nonahydrate and iron powder; The cobalt source is selected from any one or more of cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt acetate, dicobalt octacarbonyl and cobalt chloride.

5. The method for preparing the ionic liquid polymer catalyst according to any one of claims 1 to 4, characterized in that: The method includes: In an inert gas atmosphere, a vinyl-functionalized triphenylphosphine ligand with a chemical structure as shown in formula I or II, a vinyl-functionalized triphenylphosphine ionic liquid and a metal source are placed in an organic solvent and polymerized at 60-100° C. under the action of a free radical initiator.

6. The preparation method according to claim 5, characterized in that: The organic solvent is selected from any one or more of 1,4-dioxane, tetrahydrofuran, ethylene glycol dimethyl ether, ethyl acetate, N,N-dimethylformamide, dimethyl sulfoxide, n-hexane, toluene, anisole, dichloromethane and chloroform; Or / and, the free radical initiator is selected from any one or more of azobisisobutyronitrile, ammonium persulfate, potassium persulfate, benzoyl peroxide and methyl ethyl ketone peroxide; Or / and, the polymerization reaction time is 1 to 72 hours; Or / and, the molar ratio of the vinyl-functionalized triphenylphosphine ligand, the vinyl-functionalized triphenylphosphine ionic liquid and the metal source is 2: 0.72:

1.

7. The preparation method according to claim 5, characterized in that: The preparation method of the vinyl-functionalized triphenylphosphine ionic liquid comprises: Under an inert gas atmosphere, vinyl-functionalized triphenylphosphine ligand, p-dihalobenzyl and p-tert-butylcatechol were dissolved in anhydrous dichloromethane solution and stirred at 40°C for reaction; After the reaction is completed, the mixture is washed with methyl tert-butyl ether and dried to obtain a vinyl-functionalized triphenylphosphine ionic liquid.

8. Use of the ionic liquid polymer catalyst according to any one of claims 1 to 4 in catalyzing the cycloaddition reaction of flue gas and epoxy compounds to prepare cyclic carbonates.

9. The use according to claim 8, characterized in that: The cycloaddition reaction has a reaction pressure of 0.5-4.0 MPa, a temperature of 40-150° C., a reaction solvent selected from any one or more of n-hexane, dioxane, acetonitrile, tetrahydrofuran, cyclohexane and dichloromethane, and a reaction time of 4-20 h; Or / and, the CO2 content in the flue gas is 15%~25%.

10. The use according to claim 8, characterized in that: The structural formula of the epoxy compound is as follows: In the formula, R4-R5 are each independently selected from H, halogenated or unsubstituted alkane or alkene with a carbon chain length of C1-C6, -(CH2)OR6, substituted or unsubstituted phenyl or benzyl or phenoxy or benzyloxy; Wherein, R6 is selected from alkanes or alkenes with carbon numbers of 1 to 8, or alkanes with carbon chain lengths of 1 to 3 substituted with alkoxy silicon at the end.

Citation Information

Patent Citations

  • Cross-linked quaternary phosphonium ionic liquid and preparation thereof and application in CO2 cycloaddition reaction

    CN101613372A

  • Method for synthesizing cyclic carbonate through polyionic liquid nanometer catalysis cycloaddition reaction

    CN105367541A

  • Phosphine-ionic liquid organic porous copolymer-containing heterogeneous catalyst, preparation method and applications thereof

    CN107537562A

  • Organic porous copolymer heterogeneous catalyst containing quaternary phosphonium salt-phosphorus ligand, and preparation method and application thereof

    CN107537564A

  • Phosphorus-containing catalyst composition and hydroformylation process using the same

    US20100324339A1